"I tell you it has got form - form": plot, structure, and meaning in Sons and Lovers - Harrison, Andrew (D. H. Lawrence Review, 2014)
This essay considers the structure and available meanings of Sons and Lovers in light of its complex compositional history and the various conflicting influences on D.H. Lawrence as he wrote it.